School to work transition in Serbia: returns to investment in education of youth - Vuksanovic, Nemanja Goran; Joksimović, Ljubinka; Aleksić, Dragan (Industrija, 2018)
The subject of the paper is estimation of a rate of return to investment in education of youth in Serbia. The aim of the paper is to determine, on the basis of the data from the School to Work Transition Survey (SWTS) from 2015, a premium for the education of persons from 15 to 29 years old. A rate of return to investment in education for youth is estimated using the least squares method and using the instrumental variables method. As the instruments for a variable that refers to the number of years of education were used a father’s level of education and a mother’s level of education.The results of the assessment using the least squares method indicate that a rate of return to investment in education for youth in Serbia is 5.2%. The value of the coefficient in the case of evaluation by the instrumental variables method is twice as big as in the case of the least squares method. It is confirmed that in the case of the assessment using the least squares method we get a biased assessment. This result also suggests that schooling of children in Serbia continues to serve as a family characteristic, and informs that the education system in Serbia cannot provide a fair access to schooling for those children coming from socio-economic vulnerable families.
Keywords: Youth; Transit; Return on investment; Investment; Education